The Tributaries of Roland BARTHES ‘s paths OF POST – STRUCTURALIST CRITICISM - Chenini, Zahira; Kadid, Diab (Journal of Human Sciences, 2024)
This paper aims at contributing to a new critical approach through Roland Barthes ‘s claim of the death of the author; and his substitution by the reader who is one of the basics of all creative textual interpretation. this is far away from the contextual methods which are no longer able to interrogate the text. it is the reason why Roland Barthes called for adopting structuralist criticism as a new critical move that manages full textual interpretation by disclosing all its mysteries; secrets and showing its deepest meanings.